L’essor du modèle de tableau-reliquaire du Trecento italien dans la peinture du XVe siècle en Pologne - Migdal, Anna Maria (Viator (English and Multilingual Edition), 2011)
Abstract The image-reliquaries, whose singularity attracts our attention, are defined in their artistic and religious context as complex compositions. This article is about the paintings on wood panels (or, more rarely, on gilded glass) functioning as portable relics, decorated occasionally with precious or semi-precious stones. The diffusion of the model of the “picture-reliquary”—a single, diptych, or triptych panel comprising the portrait of the Virgin and Child set in a large framework encrusted with relics—was particularly widespread in Italy and subsequently in central Europe. However, the Polish reliquaries, known in the territory of Little Poland from the fifteenth century until the beginning of the sixteenth century, rarely receive art historical mention. They appear only sporadically in some articles, but they never yet have been the objects of a veritable study with regard to their iconographic contents, formal similarities, and devotional use. For this reason, this article links them to other medieval works of art and looks, from this perspective, at the continuity of such reliquaries after the Middle Ages.